Crunch time: A policy to avoid the announcement effect when terminating a subsidy - Marc Gürtler; Gernot Sieg (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2008)
If the government announces the termination of a subsidy paid for an irreversible investment under uncertainty, investors might decide to realize their investment so as to obtain the subsidy. These investors might have postponed an investment if future payment were assured. Depending on the degree of uncertainty and the time preference, the termination of the subsidy might cost the government more in toto than granting the subsidy on a continuing basis. A better strategy would be to reduce the subsidy in parts rather than to terminate the subsidy in its entirety.
urn:nbn:de:gbv:084-21506
Keywords: H3; D11; 330; Irreversibility; Investment; Announcement effect; Subsidy; Tax